2016
DOI: 10.1111/adj.12414
|View full text |Cite
|
Sign up to set email alerts
|

Violet and blue light‐induced green fluorescence emissions from dental caries

Abstract: Using violet or blue illumination in combination with green compensating filters could potentially aid in the assessment of areas of mineral loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…"Black-pigmented" organisms give strong visible red emissions when exposed to ultraviolet or visible violet light because of their high porphyrin content. The same effects occurs in mature dental plaque biofilms on the surfaces of teeth and in dental caries [22][23][24]. There are also green emissions from the collagen component of dentine.…”
Section: Fluorescence Using Ultraviolet Light or Visible Violet Lightmentioning
confidence: 79%
“…"Black-pigmented" organisms give strong visible red emissions when exposed to ultraviolet or visible violet light because of their high porphyrin content. The same effects occurs in mature dental plaque biofilms on the surfaces of teeth and in dental caries [22][23][24]. There are also green emissions from the collagen component of dentine.…”
Section: Fluorescence Using Ultraviolet Light or Visible Violet Lightmentioning
confidence: 79%
“…In the past studies, we have shown that there is a strong correlation with the volume of calculus deposits [1]. How much dental plaque [22][23][24] and other substances [25] that may be present under clinical conditions adversely influence the performance of LF and other optical systems must be assessed through controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…At 400-500 nm excitation wavelengths, the major and minor fluorescent peaks are mostly within the range of 610-614 nm, whereas with excitation at wavelengths above 500 nm, the major and minor peaks are now mainly in the near-infrared spectrum, particularly around 825 nm. The fluorescence profiles for dental plaque or biofilms on the tooth surfaces are less intense in the visible red spectrum than those for dental caries and dental calculus [53]. Zn-protoporphyrin 13 8…”
Section: Porphyrins and Biofilm Fluorescencementioning
confidence: 99%
“…This selective fluorophore approach has been used for kidney stones, tumours, dental filling materials [39,40], dental caries [41], dental plaque biofilms [2] and dental calculus [42]. The latter four sample types have been identified in diseased and healthy sites, employing optimal excitation wavelengths for fluorescence detection and then coupling this to a feedback-controlled second laser system for ablation.…”
Section: Bacterial Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation